Extracellular Vesicles based STAT3 delivery as innovative therapeutic approach to restore STAT3 signaling deficiency - Bettin, Ilaria; Brattini, Martina; Kachoie, Elham Ataie; Capaldi, Stefano; Thalappil, Muhammed Ashiq; Bernardi, Paolo; Ferrarini, Isacco; Fuhrmann, Gregor; Mariotto, Sofia; Butturini, Elena (New Biotechnology, 2024)
Extracellular Vesicles (EVs) have been proposed as a promising tool for drug delivery because of their natural ability to cross biological barriers, protect their cargo, and target specific cells. Moreover, EVs are not recognized by the immune system as foreign, reducing the risk of an immune response and enhancing biocompatibility. Herein, we proposed an alternative therapeutic strategy to restore STAT3 signaling exploiting STAT3 loaded EVs. This approach could be useful in the treatment of Autosomal Dominant Hyper-IgE Syndrome (AD-HIES), a rare primary immunodeficiency and multisystem disorder due to the presence of mutations in STAT3 gene. These mutations alter the signal transduction of STAT3, thereby impeding Th17 CD4+ cell differentiation that leads to the failure of immune response. We set up a simple and versatile method in which EVs were loaded with fully functional STAT3 protein. Moreover, our method allows to follow the uptake of STAT3 loaded vesicles inside cells due to the presence of EGFP in the EGFP-STAT3 fusion protein construct. Taken together, the data presented in this study could provide the scientific background for the development of new therapeutic strategy aimed to restore STAT3 signaling in STAT3 misfunction associated diseases like AD-HIES. In the future, the administration of fully functional wild type STAT3 to CD4+ T cells of AD-HIES patients might compensate its loss of function and would be beneficial for these patients, lowering the risk of infections, the use of medications, and hospitalizations.
CRIS-Team Scopus Importer:2024-05-24
Keywords: Delivery system; Exosomes; Extracellular Vesicles; Protein encapsulation; STAT3